OPTIMALISASI PENERAPAN TEKNOLOGI PERONTOK JAGUNG UNTUK MENINGKATKAN PRODUKTIVITAS PASCA PANEN DI METESEH - Nurhayati, Nurhayati; Astono, Ari Dwi; Ambarsari, Arum; Baskara, Andika (Jurnal Abdimas Bina Bangsa, 2024)
Corn is the leading agricultural product for corn farmers in Meteseh Village, Tembalang Subdistrict, Semarang City. However, the farmers process and thresh the corn manually without using machine tools, so it takes a long time and is inefficient. To overcome this problem, the service team designed and made a corn threshing machine that was used to optimize the application of corn threshing technology to increase post-harvest productivity. This service activity begins with the handover of the corn thresher machine to the farmer group, then the presentation and training on the use of the machine. The corn threshing process is carried out by inserting corn into the thresher shaft, then the thresher knife will separate the corn kernels from the stalks. The results of the threshing trial showed that this machine can work well, is very practical to use, easy to carry around, fast production process, undamaged corn cobs, and low electrical power. This machine has a power of 0.5 HP which is able to thresh corn kernels with a production capacity of 183 kg/hour